2008
DOI: 10.1111/j.1467-9868.2007.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Bias and Logistic Models

Abstract: Summary.  In a regression model, the joint distribution for each finite sample of units is determined by a function px(y) depending only on the list of covariate values x=(x(u1),…,x(un)) on the sampled units. No random sampling of units is involved. In biological work, random sampling is frequently unavoidable, in which case the joint distribution p(y,x) depends on the sampling scheme. Regression models can be used for the study of dependence provided that the conditional distribution p(y|x) for random samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 81 publications
0
32
0
1
Order By: Relevance
“…We hold the view that, in most geostatistical applications, spatial correlation reflects, at least in part, smooth spatial variation in relevant, but unobserved, explanatory variables rather than being an inherent property of the phenomenon being studied; an example to the contrary would be the spatial distribution of the prevalence of an infectious disease during an epidemic where, even for a uniformly distributed population in a completely homogeneous environment, the process of transmission from infectious to susceptible individuals would induce spatial correlation in the prevalence surface. This in turn leads us to emphasize that our paper is not a plea for uniform sampling, but rather for ensuring that any model for a set of data should respect whatever sampling design has been used to generate the data; for a thorough discussion that also uses point process models of sampling designs, albeit in a very different setting, see McCullagh (2008).…”
Section: Discussionmentioning
confidence: 99%
“…We hold the view that, in most geostatistical applications, spatial correlation reflects, at least in part, smooth spatial variation in relevant, but unobserved, explanatory variables rather than being an inherent property of the phenomenon being studied; an example to the contrary would be the spatial distribution of the prevalence of an infectious disease during an epidemic where, even for a uniformly distributed population in a completely homogeneous environment, the process of transmission from infectious to susceptible individuals would induce spatial correlation in the prevalence surface. This in turn leads us to emphasize that our paper is not a plea for uniform sampling, but rather for ensuring that any model for a set of data should respect whatever sampling design has been used to generate the data; for a thorough discussion that also uses point process models of sampling designs, albeit in a very different setting, see McCullagh (2008).…”
Section: Discussionmentioning
confidence: 99%
“…When sampling is biased and the marginal distribution of Z is available, the joint distribution should be used. This issue has been recently discussed by McCullagh [49] and Bergeron, Asgharian, and Wolfson [6]. If, however, the marginal distribution of Z is not available, the conditional approach seems to be appropriate, as discussed by Mandel and Ritov [48], for example.…”
Section: Singularities: a Geometric Perspectivementioning
confidence: 95%
“…Perhaps this could be relaxed by generalizing the multiperiod multinomial probit model (Geweke, Keane, and Runkle 1997). Another avenue of interest is to account more explicitly for the spatial sampling process in the inference, as recently suggested by McCullagh (2008). Indeed, he showed that, in cases in which the configuration of covariates is random, the conditional distribution of the response on the sampling units may be different than what is inferred from the marginal model (2.4).…”
Section: Discussionmentioning
confidence: 99%